The impact of positive parenting practices on children's education and behavioral change / Mahvish Nawaz Mokal and Zaki Ahmad - Mokal, Mahvish Nawaz; Ahmad, Zaki (Universiti Teknologi MARA, 2023)
This article examines the relationship between positive parenting practices and heightened academic achievements and improved behavioural stability in children. This exploration underscores the pivotal role of parental practices in shaping a child's academic disposition and overall behavior within educational contexts. Examining this dimension within the specific cultural milieu of Pakistan, the study also considers the complementary role of teachers in this process. The study involves a sample of forty participants (n=40) selected from The University of Lahore, Pakistan. Utilising a Parenting Style Quiz and a Self-Constructed Questionnaire, the research assesses diverse parenting styles and the extent of parental engagement in their children's academic and social endeavors. The study's results highlight the prevalence of an authoritarian parenting approach among parents of adolescents, coupled with a lack of attentiveness towards their children's educational progress, which acts as a barrier to their educational advancement. The research underscores the need to embrace and propagate positive parenting initiatives, accompanied by the organisation of workshops within Pakistan. These endeavours aim to educate parents about effective child discipline methodologies and are poised to leave a favorable imprint on children's characters, thereby paving the way for their higher educational pursuits.